Protective Effect of Curcumin on the Density of Hippocampal Dark Neurons in Mice Model of Aging Induced by D-galactose: A Histopathological Study - Zahra Heidari; Shabnam Mohammadi; Mahdieh Yousefi Taba (Mazandaran University of Medical Sciences, 2019)
Background: Curcumin is the most active ingredient in turmeric root of Curcuma longa of the Zingiberaceae family and has a potent antioxidant activity. This study aimed at investigating the effects of curcumin with various doses on the density of dark neurons in the hippocampus of induced D-galactose aging mice model. This experimental study was conducted on 40 adult male BALB/c mice.  Materials and Methods: We randomly divided animals into 5 groups: D-galactose, control, and curcumin 1, curcumin 2, and curcumin 3 groups. D-galactose (300 mg/kg) was intraperitoneally injected into the D-galactose group for 6 weeks. D-galactose and doses of 25, 50, and 100 mg of curcumin were administrated, respectively, to the curcumin groups 1-3 every day for 14 days. After 6 weeks, the mice's brains were stained with toluidine blue after tissue passage. Then, the mean dark neuron volume density in each unit of the ​​tissue was assessed using stereological formulas. The obtained data were analyzed by Aanlysis of variance (ANOVA) in SPSS. Results: Compared with the control group, the average number of dark neurons in the hippocampus significantly increased following the administration of D-galactose (P=0.001). The average dark neurons frequency in the hippocampus significantly decreased in the 50 and 100 mg/kg curcumin-treated groups (P=0.001 for both) compared to that of the D-galactose treated animals. Conclusion: The results of this study showed that treatment with 100 mg/kg of curcumin reduced the number of dark neurons in the hippocampus of the aging mice. It seems that curcumin decreases dark neurons via the reduction of apoptosis. Also, curcumin is a powerful antioxidant and affects the level of antioxidant status in the brain.